The debate about the sources of growth in East Asia after a quarter of a century much ado about nothing. (Economics working papers., 2017)
This paper reviews what the profession has learnt during the last 25 years about East Asias growth using growth accounting exercises and estimations of production functions. The publication of Alwyn Youngs (1992, 1994, 1995) and Jong-Il Kim and Lawrence Laus (1994) studies, and Paul Krugmans (1994) popularization of the zero total factor productivity growth thesis, led to a very important debate within the profession.